Sexo e fontes de lipídeos sobre os parâmetros sanguíneos de ovinos confinados - Da Silva, David Attuy Vey [UNESP]; Homem, Antônio Carlos [UNESP]; Ezequiel, Jane Maria Bertocco [UNESP] (My University, 2014)
The objective was to evaluate the effect of sex and the inclusion of lipid sources on the hemogram and serum biochemistry of feedlot sheep. Twenty lambs were used, distributed in randomized factorial (sex and five diets), receiving the control diet (without added lipid sources), containing sunflower seeds, peanuts, peanut oil or protected fat. Diets influenced the count of erythrocytes and hemoglobin, concentrations of cholesterol and AST. Sex affected the count of erythrocytes and platelets, concentrations of cholesterol, urea and GGT. The peanut oil diet had lower concentrations levels of triglycerides, cholesterol, and activity of AST and GGT enzymes, presenting less influence on the hepatic activity of animals.
Sex and lipid sources on blood parameters of feedlot sheep
Keywords: Blood; Oils; Ruminants